2017
DOI: 10.5483/bmbrep.2017.50.6.217
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the cellular location of brain cytoplasmic 200 RNA using an RNA-recognizing antibody

Abstract: Brain cytoplasmic 200 RNA (BC200 RNA) is a neuron-specific non-coding RNA, implicated in the inhibition of local synaptodendritic protein synthesis, and is highly expressed in some cancer cells. Although BC200 RNA has been shown to inhibit translation in vitro, the cellular location of this inhibition is unknown. In this study, we used a BC200 RNA-recognizing antibody to identify the cellular locations of BC200 RNA in HeLa cervical carcinoma cells. We observed punctate signals in both the cytoplasm and nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Therefore, it is possible that BC200 RNA may be distinctly localized in the cytoplasm and inhibit translation of specifically localized mRNAs. Our recent finding that BC200 RNA appears as fine punctate staining in the cytoplasm of HeLa cells 38 may support this hypothesis. Although we herein focused on S100A11 as a downstream partner, BC200 RNA seems to have various effects on cancer cells.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, it is possible that BC200 RNA may be distinctly localized in the cytoplasm and inhibit translation of specifically localized mRNAs. Our recent finding that BC200 RNA appears as fine punctate staining in the cytoplasm of HeLa cells 38 may support this hypothesis. Although we herein focused on S100A11 as a downstream partner, BC200 RNA seems to have various effects on cancer cells.…”
Section: Discussionmentioning
confidence: 55%
“…In the brain, BC200 and Bc1 RNAs are thought to regulate local translation in neuronal dendrites by repressing the function of translation initiation factors eIF4A and eIF4B (25). In human cell lines, BC200 RNA was also found to interact with different proteins to regulate alternative splicing (62), mRNA stability (45), and translation in p-bodies (63), implying that its role goes beyond the analogies drawn from studying Bc1 RNA. In the oligodendroglial MO3.13 cells, we found that BC200 KO led to alterations in steady-state protein levels that were partially recapitulated in POLR3A mutant cells, suggesting a dose-dependent effect of decreased BC200 RNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The internal A-rich domain of BC200 RNA is a functionally important region involved in interaction with heterogeneous nuclear ribonucleoproteins (hnRNP) E1/E2, PABP, and eIF4A ( Jang et al, 2017 ; Kondrashov et al, 2005 ). These interactions are closely related to the intracellular function and distribution of BC200 RNA ( Eom et al, 2011 ; Shin et al, 2017b ). We examined whether the length of the stretch of adenine residues affects the function of BC200 RNA.…”
Section: Resultsmentioning
confidence: 99%